P41 Prenatal exposure to antibiotics and development of epilepsy in children. Issue 6 (17th May 2019) - Gorodischer, R; Sassonker- Joseph, N; Atar-Vardi, M; Noyman, I; Novak, L
Abstract : Background: Studies reported that prenatal exposure to antibiotics in general represents a risk factor for development of epilepsy and/or cerebral palsy in children. A pathophysiological relationship seemed improbable and required adjustment to possible confounders. Methods: In a retrospective cohort investigation, we enrolled children aged 3 to 18 years born between 1998 and 2012 at the single regional hospital, and their mothers, members of 'Clalit' (the largest Health Service Organization in the region). Computerized medications database was linked with hospital records of mothers and their children. The exposed group included all children whose mothers purchased one or more antibiotic medications during their pregnancy. Epilepsy was defined by Epilepsy diagnosis and/or by chronic dispensing of antiepileptic drugs. After applying inclusion and exclusion criteria for mothers and children, 88, 899 children and their 74, 416 mothers were selected for the study. Results: The group exposed prenatally to antibiotics comprised 36, 622 (or 41.2%) children. Of them, 326 (0.9%) developed epilepsy compared to 370 (0.7%) in the unexposed group (p=0.002); Number Needed to Harm 500. Exposure during the first, second and third trimester was characterized by incidence of epilepsy in 0.8% (p= 0.928), 0.9% (p= 0.270) and 0.9% (p=0.094) of exposed children, respectively, compared to unexposed group Based on Poisson regression analysis, epilepsy was associated with male sex, maternal smoking and delivery by cesarean section. The possibility of confounding by indication was refuted by sensitivity analysis. Conclusion: We found an association of intrauterine exposure to antibiotics (particularly in late pregnancy) and development of epilepsy in children. Possible pathophysiological mechanisms are discussed. The effect of some undetermined confounder(s) cannot be ruled out. Disclosure(s): Nothing to disclose